Effects of peer collaboration on EFL learners' comprehension of conversational implicatures. (April 2021) - Chen, Yuan-shan; Lin, Ming-Fang
Abstract: This study investigated the effects of peer collaboration on EFL learners' comprehension of conversational implicatures by comparing their performances and verbalizations between individual and collaborative work on a multiple-choice discourse completion task (MDCT). Thirty-three Taiwanese EFL learners (11 individuals and 11 pairs) were asked to report their cognitive processes while performing the MDCT. The verbal protocols were transcribed and analyzed in terms of the strategies found in pragmatic-related episodes (PREs). The results indicated no significant difference in the scores of the MDCT between the individual and collaborative groups, but showed that the two groups tended to use different strategies to infer the implicatures. In addition, pair collaboration led to more negotiation and scaffolding, which facilitated the learners' pragmatic development in implicatures. This study concludes with pedagogical implications for pragmatic teaching and learning. Highlights: ● There was no significant difference in the scores of the multiple-choice discourse completion task between the individual and collaborative groups. ● Analysis of the pragmatic-related episodes showed that the two groups tended to use different strategies to infer the implicatures. ● Peer collaboration led to more negotiation and scaffolding.